KARAKTERISTIK KIMIA DAN SENSORI NUGGET TAHU DAN NANGKA MUDA - Liana Sari; Dewi Fortuna Ayu (Fakultas Pertanian Universitas Riau, 2021)
Nugget is one of the most popular ready-to-eat foods for children and adults. This study aimed to study the chemical and sensory characteristics of nugget made form tofu and young jackfruit. The research design was completely randomized (CRD) consisting of five treatments and three replications. The treatment used as the ratio of tofu and young jackfruit, namely 100: 0, 85: 15, 80: 20, 75: 25, and 70: 30. Data were analyzed using ANOVA; if the F count is greater than or equal to the F table, further testing will be carried out using the DNMRT at the 5% level. ANOVA results showed that the ratio of tofu and young jackfruit had a significant effect on protein dan crude fiber content, and hedonic on aroma, texture, taste, and overall assessment of the nugget. The ratio of tofu and young jackfruit had no significant effect on moisture content of the nugget. The best treatment was 80: 20 ratio of tofu and young jackfruit with water content of 57.13%, protein of 9.64%, crude fiber of 1,23%, and hedonic assessment on aroma, texture, taste, and overall assessmentof the nugget was rather liked by the panelists.